2011
DOI: 10.3758/s13421-011-0074-3
|View full text |Cite
|
Sign up to set email alerts
|

Transitional probabilities and positional frequency phonotactics in a hierarchical model of speech segmentation

Abstract: The present study explored the influence of a new metrics of phonotactics on adults' use of transitional probabilities to segment artificial languages. We exposed French native adults to continuous streams of trisyllabic nonsense words. High-frequency words had either high or low congruence with French phonotactics, in the sense that their syllables had either high or low positional frequency in French trisyllabic words. At test, participants heard lowfrequency words and part-words, which differed in their tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 42 publications
8
43
1
Order By: Relevance
“…That is, even though performance in the ABC condition was not significant from chance, this does not necessarily imply that no learning took place in the ABC condition. Several studies have shown that artificial language learning from continuous speech is affected by phonological patterns in the native language (Boll-Avetisyan & Kager, 2014;Finn & Hudson Kam, 2008;Mersad & Nazzi, 2011;Onnis et al, 2005). If participants would somehow be biased towards BCA patterns, then ABC participants could have un-learned this bias (resulting in chancelevel performance), and BCA participants could have developed a preference for BCA patterns while ignoring statistical cues in the artificial language.…”
Section: Resultsmentioning
confidence: 99%
“…That is, even though performance in the ABC condition was not significant from chance, this does not necessarily imply that no learning took place in the ABC condition. Several studies have shown that artificial language learning from continuous speech is affected by phonological patterns in the native language (Boll-Avetisyan & Kager, 2014;Finn & Hudson Kam, 2008;Mersad & Nazzi, 2011;Onnis et al, 2005). If participants would somehow be biased towards BCA patterns, then ABC participants could have un-learned this bias (resulting in chancelevel performance), and BCA participants could have developed a preference for BCA patterns while ignoring statistical cues in the artificial language.…”
Section: Resultsmentioning
confidence: 99%
“…Some mechanistic accounts of word segmentation conceptualize sensitivity to conditional statistical structure as arising from distinct mechanisms from those that produce sensitivity to acoustic cues such as lexical stress and phonotactic rules (e.g., Mersad & Nazzi, 2011). For example, an account put forth by Shukla et al (2007) suggested that computations are performed separately on transitional probability information and prosodic information.…”
Section: Article In Pressmentioning
confidence: 99%
“…Some models explicitly compute transitional probabilities (e.g., Gambell & Yang, 2004;Mersad & Nazzi, 2011), based on the typical assumption that learners compute transitional probabilities between elements . In contrast, other models do not explicitly compute transitional probabilities, despite the fact that they invoke processes that lead to the appearance of sensitivity to transitional probability (e.g., Perruchet & Vinter, 1998;Servan-Schreiber & Anderson, 1990).…”
Section: Article In Pressmentioning
confidence: 99%
See 2 more Smart Citations